Phytochemical and pharmacological investigation of Teucrium muscatense - Najeeb Ur Rehman; Jawaher Mohammad Salim Al-Sahai; Hidayat Hussain; Abdul Latif Khan; Syed Abdullah Gilani; Ghulam Abbas; Javid Hussain; Jamal Nasser Sabahi; Ahmed Al-Harrasi (International Journal of Phytomedicine, 2016)
The effect of enzyme inhibition, anticancer, antifungal, antioxidants activities of the extracts of Teucrium muscatense obtained with different organic solvents was investigated. Chloroform fraction exhibited promising inhibition (64%) with IC50 value (390 ± 2.0 μg/mL) against urease, while other fractions displayed moderate activity. In case of α-glucosidase and acetyl cholinesterase enzyme inhibition assays, all fractions were found inactive at a concentration of 1.0 mg/mL. The n-hexane fraction of Teucrium muscatense exhibited highest anticancer activity against breast cancer cell (MDAMB231) line at high (100 µg/mL) concentration and also inhibited the growth of F. oxysporum up to 64.3% in case of antifungal activity. EtOAc fraction showed highiest DPPH (70.6%) and ABTS (76.7%) radical scavenging activity at highest concentration (1000 μg/mL). Bioassay guided isolation of EtOAc fraction afforded two flavonoids (1 and 2). Both compounds showed highiest ABTS activity and could be a significant markers in the EtOAc fraction. Anti-lipid peroxidation assay was also performed in which aqueous fraction showed highest percentage of 73.2% at higher concentration (1000 μg/mL) followed by n-BuOH (64.1%) and EtOAc (51.4%) fractions. GC/MS analysis of the essential oil of T. mascatense showed higher percentage of linalool (34.18%), limonene (13.45%), linalyl acetate (10.04%), and β-eudesmol (9.21%). Proximate composition of Teucrium muscatense showed that it contained high amount of ash (19.6%), protein (10.3%), and fiber (17.5%).